Effects of nuclear structure on parity nonconservation in atomic cesium in relativistic mean field theory - Panda, P. K. [UNESP]; Das, B. P. (American Physical Society (APS), 2000)
We use relativistic mean field theory, which includes scalar and vector mesons, to calculate the binding energy and charge radii in 125Cs - 139Cs. We then evaluate the nuclear structure corrections to the weak charges for a series of cesium isotopes using different parameters and estimate their uncertainty in the framework of this model.